Primary Headteachers’ Views about their Professional Development - Νικολαῒδου Διαλεχτή; Θεοδοσίου-Σπανού Βαλεντίνα (Education Sciences, 2021)
This article presents the findings of a study which aimed to investigate the professional development opportunities provided to primary headteachers and identify their training needs, so as to respond effectively to their contemporary role. A quantitative methodological approach was adopted in this study and an online questionnaire was administered to all primary headteachers serving in schools in the regions of Lesvos, Evros and Rodopi. The response rate was 72.2% (122 headteachers). The findings showed that headteachers recognize the versatile and multidimensional role they have in contemporary schools and the need for training in areas related to the leadership aspects of headship. Headteachers’ professional development was mainly carried out by the Higher Education Institutions, through participation in structured training programs, while most headteachers were not trained in Educational Management and Leadership. Participants described training as unsatisfactory and pointed to the need for systematic training, both before and after appointment to headship. Regarding training, participants suggested that it should be offered in the morning, by allowing them time away from their job duties.